Pedagogical Conditions of Optimization of Moral Education of Junior Schoolchildren by Means of Ethnopedagogics of Crimean-Tatar People - Asanova, Zarema (Pedagogical Discourse, 2012)
Pedagogical conditions of optimization of moral education of junior schoolchildren by means of ethnopedagogics of Crimean- Tatar people are revealed in the article.